First report of natural parasitism by Telenomus remus Nixon, 1937 on Spodoptera latifascia Walker, 1856 eggs in Puerto Rico: insights into spatial-temporal dynamics in a semiarid tropical region - Dalla Nora, Daiane; Balardin, Ricardo Rubin; Wengrat, Ana Paula G. S.; Godoy, Wesley Augusto C.; Verle Rodrigues, Jose Carlos (Frontiers in Insect Science, 2026)
Telenomus remus is one of the most effective parasitoids of eggs used to control key pests in agricultural systems. This wasp can parasitize many species within the genus Spodoptera, including Spodoptera latifascia. The abundance and effectiveness of T. remus are influenced by landscape composition, climatic factors, and host availability, which need to be better characterized. However, no studies have investigated how those factors simultaneously affect the population dynamics of S. latifascia and T. remus under field conditions. In this study, we used sex pheromone traps to investigate the dynamics of host-parasitoid interactions and the parasitism rate of S. latifascia eggs. We also examined how landscape structure and function influence host-parasitoid dynamics, as well as the impact of local weather on parasitoid and moth abundance and on oviposition behavior. Our results indicated that the type of pheromone used did not affect the attraction of either the parasitoid or the oviposition behavior of the host. The landscape metrics driving each insect species differed, while local weather variables showed similar effects on both species. Specifically, the total number of patches was positively related to the abundance of T. remus, whereas functional traits were closely related to the abundance of S. latifascia. Rising temperatures negatively affected egg and moth abundance, while high relative humidity was positively correlated with increased abundance of these species. This study presents, for the first time, an established population of T. remus in Puerto Rico, and insights into the temporal and spatial dynamics associated with S. latifascia.